Demographic variables, service quality and web search skills as determinants of IRs utilization in universities in Kwara State - Temim, Fatima Modupe; Issa, Abdulwahab Olarenwaju; Eiriemiokhale, Kennedy Arebamen (Universitas Padjadjaran, 2026)
Background: Institutional Repositories (IRs) are an initiative by librarians to protect and make the intellectual content of lecturers easier to access. Purpose: This study examines demographic variables, service quality and web-search skills as determinants of IRs utilization in universities in Kwara State. Method: This study adopted a descriptive survey method. The study population comprised university lecturers in Kwara State. This study adopted a simple random sampling technique. This sampling technique ensured that all respondents had an equal chance of being selected for the study. The study used the Roasoft sample size calculator to determine the sample size for a population of 2144 at the 0.05 level of significance, yielding a sample size of 326. The study used a questionnaire as an instrument for data collection and descriptive statistics, including frequencies, tables and percentages, were used for data analysis. Results: The study found that promptness, skills, competencies, responsiveness and empathy as service quality factors influenced lecturers’ utilization of institutional repositories in universities in Kwara State. Conclusion: The study finds that robust information search skills, improved internet-based services, timely data-based information, organized information search services and processed information services, such as web search skills, positively influence IR utilization among lecturers at Kwara State University. Implication: The study recommends engaging lecturers in activities that will help them make greater use of IR.